(untitled) (Communicare: Journal for Communication Studies in Africa, 2022)
The study investigates if companies listed on the Johannesburg Stock Exchange (JSE) use impression management techniques when disclosing earnings-related information on Twitter. A content analysis was followed as a research methodology to conduct the study. The findings indicate that Twitter is not widely used by listed companies to disclose earnings information. However, where Twitter is used, companies do employ impression management techniques. The impression management techniques differ depending on whether the earnings information distributed is positive or negative. This was evident as tweets with a positive tone were circulated much more than tweets with a negative or neutral tone. The use of self-presentational and dissemination patterns also differed significantly across the tone of tweets. Positive tweets contained more narratives compared to negative tweets, indicating that negative information is concealed. Negative tweets predominantly did not contain hashtags, once again indicating that companies often conceal negative information. Most positive and neutral tweets contained hashtags, illustrating that companies often use Twitteras a means to alter users’ perceptions towards a positive image. Understanding how companies use impression management techniques will assist users in interpreting and using the information shared. The research may also be beneficial to regulators who may consider drafting guidance and standards regarding the use of social media by companies.